SELECTION OF AN EFFECTIVE AND EFFICIENT DUAL-FUEL PROPULSION SYSTEM FOR LNG ISO TANK LCT SHIPS - Palebangan, Hendra; Muhajirin, Muhajirin; Gutami , Nanda Itohasi; Kadir , Abdul (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2025)
Flexible dual-fuel technology is becoming increasingly important in the marine market, where alternative fuels are receiving more attention due to increasing concerns over exhaust pollutant emissions generated by internal combustion engines, fluctuating fuel costs, crude oil depletion, and classification issuing specific rules or guidelines for propulsion systems applied to LNG carriers. Various solutions have been proposed, including the use of alternative fuels. LNG, as a fuel, has been proven and is a viable solution to replace fuel oil. Through this propulsion system technology, it can be more flexible and efficient in accommodating various shipping routes and operations. The study used Rhinoceros, Maxsurf Modeller, and Numeca Fine Marine to integrate the track plan. Calculations of speed and break BHP, and validation of speed-power predictions with HydroComp PropExpert for propeller-engine matching confirmed the selection of dual-fuel engines. Based on the gearbox configuration and LNG load capacity, a dual-fuel ME propulsion system is selected. For large loads, use high pressure, and for small loads, use low pressure with the advantages of better energy efficiency, lower initial cost, slim dimensions, and Tier III NOx standards.